2015
DOI: 10.1186/s12889-015-1437-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis treatment delays and associated factors within the Zimbabwe national tuberculosis programme

Abstract: BackgroundDelayed presentation of pulmonary TB (PTB) patients for treatment from onset of symptoms remains a threat to controlling individual disease progression and TB transmission in the community. Currently, there is insufficient information about treatment delays in Zimbabwe, and we therefore determined the extent of patient and health systems delays and their associated factors in patients with microbiologically confirmed PTB.MethodsA structured questionnaire was administered at 47 randomly selected healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 20 publications
10
65
5
Order By: Relevance
“…26 Possible reasons for delays in starting treatment in Zimbabwe might be the time taken in conducting the baseline biochemistry tests on liver and renal function and the decision to start MDR-TB treatment, which is made by the clinical management team. Previous studies conducted elsewhere have shown that delayed treatment is due to a combination of patient and health system factors, [27][28][29] and these need to be addressed.…”
Section: Public Health Action Managing Rmp-resistant Tb In Zimbabwe 126mentioning
confidence: 99%
“…26 Possible reasons for delays in starting treatment in Zimbabwe might be the time taken in conducting the baseline biochemistry tests on liver and renal function and the decision to start MDR-TB treatment, which is made by the clinical management team. Previous studies conducted elsewhere have shown that delayed treatment is due to a combination of patient and health system factors, [27][28][29] and these need to be addressed.…”
Section: Public Health Action Managing Rmp-resistant Tb In Zimbabwe 126mentioning
confidence: 99%
“…The findings showed that other factors, such as age, alcohol consumption, tobacco use, improper nutrition, and lack of access to health facilities and local medicines increased the rate of treatment failure and reduced the success of TB treatment (3,8). The middle line of the figure shows the results of the current system and indicates a completely downward trend in TB recurrence during 2006 -2016.…”
Section: Discussionmentioning
confidence: 98%
“…One of the main tasks of all healthcare systems is management of diseases. It is clear that the management system should be designed and implemented with respect to diseases, facilities, and needs proportionate to resources (4)(5)(6)(7)(8). The incidence and prevalence of TB are not similar in all parts of Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ct values have been found to predict decreasing bacterial burden with increasing immunosuppression and a combination of Ct values and sputum smear status to be a possible measure of bacterial burden in high HIV-burden settings [5]. Several studies have documented the various factors associated with patient delay for TB diagnosis [6,7,8,9,10,11,12,13,14]. Mycobacterial load is likely to increase with patient delay since bacillary burden has been found to grow over time and may have an impact on the novel diagnostic tests [15,16].…”
Section: Introductionmentioning
confidence: 99%